Product innovation : leading change through integrated product development - Rainey, David L., 1946- (Cambridge University Press, 2005)
Increasing pressures to produce new products faster and cheaper are resulting in huge efforts to streamline and restructure the traditional new product development (NPD) process. The purpose of the book is to describe, assess, and apply the latest constructs, methods, techniques, and processes to enable managers, professionals, and practitioners to be more effective in designing, developing, and commercializing new products and services. It provides guidance and support in formulating and executing NPD programs for business practitioners and MBA students. The book is written from an Integrated Product Development (IPD) perspective, linking all aspects of marketing, costing and manufacturing into the development process even before the first prototype is built. It covers the advanced tools necessary to achieve this such as virtual prototyping and fully integrated business systems, and explains the changes needed to organisational structure and thinking.